Surgical approach for duodenal diverticulum perforation: A case report - Kansoun, Alaa (Int J Surg Case Rep, 2020)
INTRODUCTION: Duodenal Diverticula is not uncommon and it is mostly found in the 2nd part of the duodenum. Despite the fact that it is mostly found incidentally, it can complicate however it rarely complicates by perforation. Treatment is indicated only in complicated cases and it is divided into conservative and surgical arms. PRESENTATION OF CASE: It is a case of 78 years old Lebanese female that was diagnosed intra-operatively with a perforated duodenal diverticulum after presenting with post prandial abdominal pain, distention and pneumoperitoneum on imaging. Our case was consistent with previous reports where the diverticulum occurred in the second part of the duodenum. We opted for primary resection of the diverticulum and over-sewing. Moreover, patient had an uneventful post-operative course and progressed gradually to be discharged on day 10. CONCLUSION: Our case aims to draw attention to a rare complication of duodenal diverticula and to widen the differential diagnosis of pneumoperitoneum thus concluding about the better treatment option. Previous reports show that proper management is still a controversial topic; however surgical approach is indicated in case of systemic signs.